Faktor-Faktor yang Mempengaruhi Minat Siswa SMA untuk Melanjutkan Studi ke Perguruan Tinggi - Arlisa Syabina; Haidar, Kadori; Abu, Ilham (Faculty of Teacher Training and Education, Mulawarman University, 2024)
This study aims to determine the factors that influence the Continuing Study Interest to Higher Education Students SMA Negeri 1 Loakulu. The type of research used is descriptive research with a quantitative approach. The population in this study is the students of class XII SMA Negeri 1 Loakulu Academic Year 2024/2025. The sample of this study amounted to 70 students with proportional random sampling technique. Data collection techniques used questionnaires. The results showed that there was a positive and significant influence of Internal Factors and External Factors on the Interest in Continuing Studies to Higher Education Class XII Students of SMA Negeri 1 Loakulu as indicated by the Fcount value of 36,282 with a significance value of F of 0.001. The coefficient of determination is 0.520 or 52.0%.